Amamentação e alimentação complementar de crianças em região de fronteira e sua interface com a segurança alimentar e nutricional - Hirano, Aline Renata (2020)
Breastmilk and complementary healthy eating are rights ensured by the constitution and laws that deal with the subject, in particular, the Food and Nutrition Security Law. However, this process in the border region can suffer different implications due to the peculiarities marked by the exchanges, differences, potentialities and vulnerabilities of this context. Then, it is questioned how breastfeeding and complementary feeding of children living in a border region are configured and what is their interface with the context of Food and Nutritional Security of their families. Therefore, the objective is to understand the experience of mothers and healthcare professionals about breastfeeding and complementary feeding for children living in a border region and to know its interface with the context of Food and Nutritional Security of their families. This is an exploratory-descriptive research with a qualitative approach, carried out with twelve mothers and twelve professionals from ten basic health units, seven of which are Healthy Family Strategies, in the city of Foz do Iguaçu, Paraná. Data were collected between April and October 2019, through individual semi-structured interviews, audio recorded, transcribed with the aid of a text editor and interpreted from the content analysis. The results found were presented through two articles entitled: “Breastfeeding and Complementary feeding: experience of mothers and healthcare professionals in a border region” and “Breastfeeding, Complementary feeding and Food and Nutrition Security in a Border Region”. The categories present in the first article were “Practice of breastfeeding and complementary feeding in a border region”, “Meanings of breastfeeding and complementary feeding: expectations, emotions and difficulties”; and “Attention to children from zero to two years old and the border context: existing peculiarities”. Those included in the second article are “Breastfeeding and complementary feeding: the child's right to safe and adequate food”, “Breastfeeding and complementary feeding: from guiding to consumption”; and "Breastfeeding, complementary feeding and Food and Nutritional Security in the context of the Triple Border". The studied context presented several difficulties in the process of breastfeeding and complementary feeding, such as the excessive demand for work and the inefficient communication between professionals in the Primary Healthy Care; the unfavorable financial conditions that make it impossible to choose varied and quality foods; the lack of adherence and the neglect of families in the face of the child's guidelines and food routine; the need for maternal return to work and early weaning. However, many professionals and mothers are protagonists in guaranteeing the right to safe and adequate food for the child, either by supporting mothers through a welcoming listening and by supporting the common doubts of that period, and also by prioritizing the supply of quality food for children even in the face of unfavorable financial conditions. As for the peculiarities present at the border, there was a lack of knowledge about the flow of care for foreign and “brasiguaias” children, the difficulty in continuing to care for the last one because they live in Paraguay and the importance of dialogue and respect for this public, guided by empathy.